Apology Strategies in Harry Potter Movie Series - Intan Khairu Nisa; Adi Sutrisno (Universitas Ahmad Dahlan, 2018)
Apology is an inevitable part of human communication as an act of face-saving strategy. It is necessarily uttered if an offense is made. This research is an attempt to reveal the apology strategies used as well as to analyze the influence of social distance and relative power to the realization of apology strategies, as seen in Harry Potter and the Order of the Phoenix, Harry Potter and the Half Blood Prince, and Harry Potter and the Deathly Hallows Part 1 and 2. In total, there are 125 data found and those are classified according the apology strategy employed. The result shows that the majority of the speakers employ indirect apology strategy ‘Explanation or Account of Cause’ to apologize. Furthermore, this research also found that social distance and relative power are taken into account during the apology process and they affect the linguistic realization of apology strategies in the movies.